PHYTOTOXICITY AND FIELD EFFICACY OF EXSEROHILUM LONGIROSTRA JC/MIN THE CONTROL OF BARNYARDGRASS ECOTYPES (ECHINOCHLOA CRUS-GALLI VAR. CRUS-GALLI(L.) BEAUV) - ABDUL SHUKOR JURAIMI; ARIFIN TASRIF; JUGAH KADIR; SUHAIMI NAPIS; SOETIKNO SLAMET SASTROUTOMO (BIOTROPIA, 2005)
Five selected ecotypes of bamyardgrass (Echinochloa crus-galli var. crus-gatti) from several rice growing areas in Malaysia and Indonesia were tested for their susceptibility  to the potential bioherbicide  (Exserohilum longirostratum). Bamyardgrass seedlings at the 2-3-lcaf stage were treated with 2.5xl07 conidia/ml from E. longirostratum  at different application frequencies (single, double and triple). In addition, aqueous extract assays were evaluated for the presence of a phytotoxic compound responsible for the virulence of the bioherbicide. Results of the study showed that disease severity significantly increased 20 days after treatment and resulted in mortality of the seedlings. Ecotypes from Perak and Lampung were most susceptible to the bioherbicide upon triple applications. Percentage dry weight reductions were 86.34 and 83.14%, respectively. Other ecotypes (Melaka, Banten and South Sulawesi) were observed to have a relatively similar response. Moreover, aqueous extracts of E. longirostratum  increased mortality up to 92.50% of bamyardgrass seedlings. These findings suggest that regular (double and triple) applications of E. longirostratum at a concentration of 2.5xl07 conidia/ml significantly increased mortality among bamyardgrass ecotypes. Mortality of the seedlings was attributed to the presence of a secondary phytotoxic metabolite. Key words :    Field efficacy / Phytotoxicity / Exserohilum longirostratum I Echinochloa crus-galli var. crusgalli I ecotypes.